2020
DOI: 10.1007/s12192-020-01096-y
|View full text |Cite
|
Sign up to set email alerts
|

Studying heat shock proteins through single-molecule mechanical manipulation

Abstract: Imbalances of cellular proteostasis are linked to ageing and human diseases, including neurodegenerative and neuromuscular diseases. Heat shock proteins (HSPs) and small heat shock proteins (sHSPs) together form a crucial core of the molecular chaperone family that plays a vital role in maintaining cellular proteostasis by shielding client proteins against aggregation and misfolding. sHSPs are thought to act as the first line of defence against protein unfolding/misfolding and have been suggested to act as "sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…However, a deeper understanding of the mechanisms underlying the functions of heat shock proteins was achieved only recently, thanks to single-molecule experiments. Several excellent works have been carried out on this topic by using optical tweezers (as further reading we suggest the review by Choudhary et al [100] and the references therein reported). As a way of example, we report on the work by Mashaghi et al [101], who employed OT to investigate the bacterial Hsp70 homologue (DnaK) from Escherichia coli and its role in guiding the folding/unfolding cycles of maltose proteins (MBP).…”
Section: Protein Foldingmentioning
confidence: 90%
“…However, a deeper understanding of the mechanisms underlying the functions of heat shock proteins was achieved only recently, thanks to single-molecule experiments. Several excellent works have been carried out on this topic by using optical tweezers (as further reading we suggest the review by Choudhary et al [100] and the references therein reported). As a way of example, we report on the work by Mashaghi et al [101], who employed OT to investigate the bacterial Hsp70 homologue (DnaK) from Escherichia coli and its role in guiding the folding/unfolding cycles of maltose proteins (MBP).…”
Section: Protein Foldingmentioning
confidence: 90%
“…At the same time, high molecular weight HSPs, such as HSP60, HSP70 and HSP90, bind unfolded or misfolded proteins and promote their refolding using the energy of ATP hydrolysis (77)(78)(79). Therefore, under cellular stress and energy deprivation, ATP-independent small HSPs are able to rapidly and metabolically prevent protein aggregation, maintain denaturing proteins in a folded state and inhibit the denaturation process until ATP-dependent HSPs complete the refolding process (80)(81)(82). If proper folding does not occur, small HSPs contribute to the clearance of denatured proteins by directing them to the pathway of degradation mechanisms (Fig.…”
Section: Features Of the Induction Of Small Atp-independent Hsps In M...mentioning
confidence: 99%
“…While single-molecule studies of some chaperones have also been covered in several previous reviews [18][19][20][21][22][23][24][25][26][27][28], this section provides a short description of mechanical interrogation strategies, instruments for force experiments, and our perspective on selected contributions in chaperone-client interactions that have been published since 2015. The subsections are divided into heat shock proteins, the study of the impact of chaperones on folding ribosomebound proteins, DsbA-client interactions, SNARE proteins with Mun/Munc chaperones, and chaperone-assisted folding of the membrane proteins.…”
Section: Single-molecule Mechanical Studies Of Chaperonesmentioning
confidence: 99%